Antiviral activity of portulaca oleracea L. extracts against porcine epidemic diarrhea virus by partial suppression on myd88/NF-κb activation in vitro. (May 2021) - Liu, Yueyue; Zhao, Lu; Xie, Yunhui; Chen, Zhi; Yang, Shifa; Yin, Bin; Li, Guiming; Guo, Huijun; Lin, Shuqian; Wu, Jiaqiang
Abstract: Porcine epidemic diarrhea virus (PEDV), especially variants, causes a highly contagious enteric disease which could give rise to huge economic losses in the swine industry worldwide. Portulaca oleracea L. has been reported to regulate intestine disease and involved in viral infections. However, the underlying mechanisms of Portulaca oleracea L. extracts against PEDV have not been fully elucidated. In this study, the antiviral effects and potential mechanisms of Portulaca oleracea L. extracts against PEDV were investigated in vitro. We first examined the inhibitory effects of different Portulaca oleracea L. extracts on the PEDV(JX-16 strain) in vitro and found that the water extract of Portulaca oleracea L.(PO)could significantly inhibit PEDV replication by 92.73% on VH cells and 63.07% on Vero cells. Furthermore, time-course analysis showed PO inhibited PEDV replication during the adsorption period of infectious cycle. Western blot and indirect immunofluorescence assay indicated that PO down-regulated the S protein expression in a dose-dependent manner. In addition, our results demonstrated the ability of PO to inhibit PEDV replication in VH cells by down-regulating the cytokine levels (TNF-α, IL-22 and IFN-α) and inhibiting the NF-κB signaling pathway activated by PEDV. Thus, Portulaca oleracea L extracts have potential utility in the preventive and therapeutic strategies for PEDV infection. Highlights: This study aims to assess the inhibitory effects of different Portulaca oleracea L. extracts on the PEDV(JX-16 strain) in vitro. The water extract of Portulaca oleracea L.(PO)could significantly inhibit PEDV replication. Time-course analysis showed PO inhibited PEDV replication during the adsorption period of infectious cycle. PO could inhibit PEDV replication in VH cells by down-regulating the cytokine levels (TNF-α, IL-22 and IFN-α) and inhibiting the NF-κB signaling pathway activated by PEDV.